8-12 [mu] m waveband high-durability anti-reflection film for TQIR chalcogenide glass substrate

By plating the stacked structure of CdTe, ZnSe, Ge, YbF3 and other layers on the TQIR sulfur-based glass substrate, the problem that the prior art is difficult to use in high temperature, high humidity and low temperature drying environments is solved, and high transparency is achieved The overrepresence, low reflectivity and high durability film layers extend the service life of infrared optical systems.

CN119430687APending Publication Date: 2025-02-14YUNNAN KIRO CH PHOTONICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411684996.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to plating a high-durable anti-reflection film on a TQIR sulfur-based glass substrate that meets high temperature and high humidity environments and low temperature drying environments, which limits the promotion and application of TQIR sulfur-based glass in infrared optical systems.

Method used

The stacked structure of CdTe layer, ZnSe layer, Ge layer, ZnSe layer, Ge layer, ZnSe layer, Ge layer, ZnSe layer, Ge layer, ZnSe layer, YbF3 layer, and ZnS layer is adopted. Through Kaufman ion source coating technology, it is at 145-150°C. A high transmittance and low reflectance anti-reflection film was plated at temperatures.

Benefits of technology

The transmittance of the TQIR sulfur-based glass substrate is greater than 96% and the reflectance is less than 1%. The film layer is not easy to fall off in extreme environments, meeting the requirements of various environmental conditions such as high temperature, high humidity, low temperature drying, etc., and extending the use of The service life of infrared optical systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430687A_ABST
    Figure CN119430687A_ABST
Patent Text Reader

Abstract

The invention discloses an 8-12 [mu] m waveband high-durability anti-reflection film for a TQIR chalcogenide glass substrate. The 8-12 [mu] m waveband high-durability anti-reflection film is formed by sequentially stacking a CdTe layer, a first ZnSe layer, a first Ge layer, a second ZnSe layer, a second Ge layer, a third ZnSe layer, a third Ge layer, a fourth ZnSe layer, a YbF3 layer and a fifth ZnS layer from the surface of the TQIR chalcogenide glass substrate to the air side. The anti-reflection film is high in bonding strength and does not fall off when used in an extreme environment, and the transmissivity of a TQIR chalcogenide glass substrate is effectively increased by more than 96% through the film layer; and the reflectivity of the TQIR chalcogenide glass substrate is reduced to be lower than 1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of anti-reflection films, and in particular to a high-durability anti-reflection film in the 8-12 μm band for a TQIR chalcogenide glass substrate. Background Art

[0002] TQIR chalcogenide glass (NBL-TQIR-1) is a new type of high refractive index chalcogenide glass material developed by Ningbo University. For details, please refer to "Chen Jinjin, Zhou Gangjie, Tan Yan, et al. Infrared imaging optical system based on new chalcogenide glass (invited) [J]. Infrared and Laser Engineering, 2023, 52(05): 105-113." The large-sized new type of high refractive index chalcogenide glass NBL-TQIR-1 is disclosed, and its composition is Ge-Se-Te. The chalcogenide glass is transparent in the ultra-wide spectral range of 1.5-18μm, and can be prepared on a large scale with a large aperture (Φ≤100mm).

[0003] The medium-wave dual-field infrared optical system based on high-refractive-index chalcogenide glass effectively realizes the de-germanization design. Compared with the infrared optical system based on traditional infrared materials, the optical system weight is reduced by 35%, the length is reduced by 15%, and the transmittance is increased by 10%. The common-optical-path and common-focal-plane dual-band infrared optical system based on laminated gradient refractive index (GRIN) chalcogenide glass realizes the design of cemented lenses for the first time in the uncooled medium / short-wave infrared imaging optical system. Compared with the dual-band infrared optical system based on traditional infrared materials, the optical system weight is reduced by 40%, the length is reduced by 30%, and the transmittance is increased by 15%. In the cooled medium / long-wave infrared optical system, GRIN chalcogenide glass with different refractive index difference Δn shows excellent chromatic aberration correction ability. Compared with the dual-band infrared optical system based on traditional infrared materials, the optical system weight is reduced by 20%, the length is reduced by 20%, and the transmittance is increased by 18%. It can be used to replace germanium materials in infrared optical systems to reduce the production cost of infrared optical systems and improve the athermal performance of infrared optical systems.

[0004] The refractive index of TQIR chalcogenide glass in the 8-12μm band is about 3.18, which is a material with a relatively high refractive index. The excessively high refractive index results in an average transmittance of only about 56.5% in the 8-12μm band. An anti-reflection film must be coated on its surface to increase the transmittance of the double-sided coated TQIR chalcogenide glass to more than 95%. Only in this way can the light entering the optical system still have relatively high light energy after passing through multiple lenses, meeting the needs of the optical system for clear imaging.

[0005] Using conventional Ge and ZnS film materials in a structural design with alternating high and low refractive indices, it is difficult to coat TQIR chalcogenide glass with an anti-reflection film that meets the environmental adaptability requirements of the film layer for 10 days of wet heat testing, high-temperature storage, and low-temperature storage. This limits the promotion and application of TQIR chalcogenide glass.

[0006] The anti-reflection film set on the existing chalcogenide glass substrate, such as the 7.7-14.2 μm band DLC protective anti-reflection film on the chalcogenide glass substrate disclosed in CN202311480864.3, is composed of a 30nm thick Y2O3 layer, a 312nm ZnS layer, a 162nm Ge layer, a 1210nm ZnS layer, a 173nm Ge layer, an 892nm ZnS layer, a 632nm Ge layer, a 125nm ZnS layer, a 740nm Ge layer, and a 1150nm DLC layer stacked in sequence from the chalcogenide glass substrate to the air layer. The average transmittance of the prepared film system is greater than 88%, the reflectivity is effectively controlled, and the average reflectivity of the obtained film system is less than 2%. The film system also has good resistance to high temperature and high humidity environments, and can remain in an environment of 95% to 100% humidity and 48 to 52°C for 10 days without the film falling off; the film also has good resistance to temperature changes, and can be maintained at -64 to -60°C and 68 to 72°C for 2 hours each, and cycled 3 times without the film falling off.

[0007] However, this anti-reflection film is not suitable for TQIR chalcogenide glass substrate.

[0008] The information disclosed in the background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0009] In view of the above technical problems, the present application provides a high-durability anti-reflection film in the 8-12 μm band for a TQIR chalcogenide glass substrate. The anti-reflection film has high bonding strength and does not fall off when used in extreme environments. The film layer effectively increases the transmittance of the TQIR chalcogenide glass substrate by more than 96%; and reduces the reflectivity of the TQIR chalcogenide glass substrate to less than 1%.

[0010] The present application provides a high-durability anti-reflection film in the 8-12 μm band for a TQIR chalcogenide glass substrate, which is composed of a CdTe layer, a first ZnSe layer, a first Ge layer, a second ZnSe layer, a second Ge layer, a third ZnSe layer, a third Ge layer, a fourth ZnSe layer, a YbF3 layer, and a fifth ZnS layer stacked in sequence from the surface of the TQIR chalcogenide glass substrate to the air side.

[0011] In the present application, the air side refers to a side perpendicular to the surface and facing outward from the surface of the TQIR chalcogenide glass substrate. The air side faces outward relative to the surface of the TQIR chalcogenide glass substrate.

[0012] Preferably, the thickness of the CdTe layer is 40 to 43 nm;

[0013] The thickness of the first ZnSe layer is 120-128 nm;

[0014] The thickness of the first Ge layer is 320-329 nm;

[0015] The thickness of the second ZnSe layer is 468-480 nm;

[0016] The thickness of the second Ge layer is 365-370 nm.

[0017] Preferably, the thickness of the third ZnSe layer is 345-351 nm;

[0018] The thickness of the third Ge layer is 50-60 nm;

[0019] The thickness of the fourth ZnSe layer is 1379-1400 nm;

[0020] The thickness of the YbF3 layer is 1380-1390nm;

[0021] The thickness of the fifth ZnS layer is 200-210 nm.

[0022] Preferably, the transmittance of the anti-reflection film is greater than 97%; and the reflectivity of the anti-reflection film is less than 0.61%.

[0023] Preferably, the anti-reflection film can withstand an ambient temperature of -42 to 72°C; and the anti-reflection film can withstand an ambient relative humidity of less than 15% to 100%.

[0024] Preferably, the preparation method comprises the following steps:

[0025] Using a Kaufman ion source, bombard any surface of a TQIR chalcogenide glass substrate in a wavelength range of 8 to 12 μm to obtain a film setting surface;

[0026] A CdTe layer, a first ZnSe layer, a first Ge layer, a second ZnSe layer, a second Ge layer, a third ZnSe layer, a third Ge layer, a fourth ZnSe layer, a YbF3 layer, and a fifth ZnS layer are sequentially stacked on the film setting surface.

[0027] Preferably, during the bombardment with the Kaufman ion source, the gas source used is argon; the gas source flow rate during the bombardment with the Kaufman ion source is 9 to 12 sccm; and the bombardment time is at least 6 minutes.

[0028] Preferably, during bombardment of the Kaufman ion source, the bias voltage is 120-140V; and the discharge voltage is 80-90V.

[0029] Preferably, the coating temperature of each film layer is 145-150°C.

[0030] Preferably, during bombardment by the Kaufman ion source, the discharge current is 25-35A; and the coil current is 1.5-3A.

[0031] The beneficial effects of this application include:

[0032] 1) The TQIR chalcogenide glass substrate provided in this application uses a high-durability anti-reflection film in the 8-12μm band. The film layer structure can withstand the adhesion, humidity and heat, and temperature test requirements in GJB2585A-2019 "General Specifications for Optical Film Layers". 48~52-64~-6068~722) The TQIR chalcogenide glass substrate provided in this application uses a high-durability anti-reflection film in the 8-12μm band. The film layer structure can also withstand the stringent 10-day humidity and heat test, 48-hour high-temperature storage test, and 48-hour low-temperature storage test. 10-day humidity and heat test: maintained for 10 days at a temperature of 48~52°C and a relative humidity of 95%~100%, meeting the requirements for long-term use in a high temperature and high humidity environment; 48-hour high-temperature storage test: maintained for 48 hours at a temperature of 68~72°C and a relative humidity of less than 15%, meeting the requirements for long-term use in a high temperature and extremely dry environment. 48-hour low-temperature storage test: Keep it at -42 to -38°C and relative humidity less than 15% for 24 hours, meeting the requirements for long-term use in extremely low temperature and dry environments. Due to the above extreme environment, the existence time in the normal use environment is relatively short, and the above use time meets the short-term use requirements. In practical applications, it can effectively improve the service life of infrared optical systems in various harsh environments.

[0033] 2) The TQIR chalcogenide glass substrate provided in this application is used for a high-durability anti-reflection film in the 8-12 μm band. The TQIR chalcogenide glass material is used as the substrate, and the structure of each layer is: a 40nm CdTe layer, a 120nm thick ZnSe layer, a 320nm thick Ge layer, a 470nm thick ZnSe layer, a 370nm thick Ge layer, a 345nm thick ZnSe layer, a 60nm thick Ge layer, a 1400nm thick ZnSe layer, a 1395nm thick YbF3 layer, and a 210nm thick ZnS layer. This structure effectively improves the transmittance and environmental adaptability of the anti-reflection film. In addition, the 40nm CdTe layer is used as a connecting layer between the substrate and the film layer to enhance the bonding ability between the film layer and the substrate, and the film layer is improved by controlling the coating temperature between 145 and 150°C. The firmness of the film layer is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A schematic cross-sectional structure diagram of a high-durability anti-reflection film in the 8-12 μm band on a TQIR chalcogenide glass substrate in at least one embodiment provided in the present application;

[0035] Figure 2 A transmittance spectrum curve of a double-sided coated test piece of a TQIR chalcogenide glass substrate 8-12 μm band high-durability anti-reflection film prepared in Example 1 provided in the present application;

[0036] Figure 3 This is a reflectivity spectrum curve of the 8-12 μm band high-durability anti-reflection film of the TQIR chalcogenide glass substrate prepared in Example 1 provided in the present application. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0038] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The technical means that are not described in detail in this application and are not used to solve the technical problems of this application are all set according to the common knowledge in the field, and can be implemented in a variety of common knowledge settings.

[0040] See also Figures 1 to 3 The present application provides a high-durability anti-reflection film in the 8-12 μm band for a TQIR chalcogenide glass substrate, which is composed of: a CdTe layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer arranged on one surface of the TQIR chalcogenide glass substrate and stacked and connected in sequence.

[0041] The preparation method of the film layer comprises the following steps:

[0042] Before plating, a physical vapor deposition coating device was used with Kaufman as the ion source to bombard the substrate surface for 6 minutes, the gas was argon, the gas flow rate was 9-12sccm, the bias voltage was 120-140V, the discharge voltage was 80-90V, the discharge current was maintained at 25-35A, and the coil current was 1.5-3A;

[0043] The plating temperature of each layer is controlled at 145-150°C.

[0044] Example 1

[0045] A Φ25.4 mm TQIR chalcogenide glass material plane window is selected, and a surface layer of one surface of a substrate is bombarded within a wavelength range of 8 to 12 μm using a Kaufman ion source, filled with argon gas, with a gas flow rate of 10 sccm, a bias voltage of 120 V, a discharge voltage of 80 V, a discharge current of 30 A, a coil current of 2 A, and bombarded for 6 minutes; at 145° C., a 40 nm thick CdTe layer, a 120 nm thick ZnSe layer, a 320 nm thick Ge layer, a 470 nm thick ZnSe layer, a 370 nm thick Ge layer, a 345 nm thick ZnSe layer, a 60 nm thick Ge layer, a 1400 nm thick ZnSe layer, a 1395 nm thick YbF3 layer, and a 210 nm thick ZnS layer are sequentially plated to obtain a high-durability anti-reflection film arranged on a TQIR chalcogenide glass substrate and having high transmittance for light in the wavelength range of 8 to 12 μm.

[0046] A high-durability anti-reflection film in the 8-12μm band was coated on both sides of the TQIR chalcogenide glass substrate, and the transmittance was measured using a Fourier transform infrared spectrometer. The specific test process was the same as the test method of the existing anti-reflection film, and the average transmittance of the anti-reflection film was measured to be 97.42%.

[0047] A high-durability anti-reflection film in the 8-12 μm band was coated on one side of a TQIR chalcogenide glass substrate, and the back side was roughened. The reflectivity was measured using a Fourier transform infrared spectrometer. The specific test process was the same as the test method for existing anti-reflection films, and the average reflectivity of the anti-reflection film was measured to be 0.61%.

[0048] The coated parts were placed in a test box at a temperature of 48-52°C and a relative humidity of 95%-100% for 10 days, and the film layer was observed. There was no film peeling or flaking.

[0049] After the coated parts were placed in a test box at a temperature of 68-72°C and a relative humidity of less than 15% for 48 hours, the film layer was observed and no peeling or other phenomena were observed;

[0050] The coated parts were placed in a test box at a temperature of -42 to -38°C and a relative humidity of less than 15% for 24 hours, and the film layer was observed. No delamination or peeling was observed.

[0051] The transmittance spectrum curve of the double-sided coated test piece of the coated part obtained in this embodiment is as follows: Figure 1 As shown in the figure, under the incident light in the 8-12μm band, the transmittance of the coated part is greater than 96%, and the highest is close to 98%. Multiple test results show that the transmittance of the part is relatively uniform, especially when the incident light wavelength is 9-9.5μm, it is close to 98%. This shows that the transmittance of the film structure is stable and suitable for incident light in the 8-12μm band.

[0052] The reflectivity spectrum curve of the double-sided coated test piece of the coated part obtained in this embodiment is as follows: Figure 2 As shown in the figure, it can be seen that under the incident light in the 8-12μm band, the reflectivity of the coated part is less than 1%, and especially under the incident light in the 10-12μm band, the reflectivity is less than 0.6%, which shows that the reflectivity result of the film structure is stable and suitable for the incident light in the 8-12μm band.

[0053] The coated parts were tested according to the adhesion, humidity and heat, and temperature test requirements in GJB2585A-2019 "General Specifications for Optical Films". The film layer of the parts passed the adhesion, humidity and heat, and temperature tests. The experimental processes and requirements are as follows:

[0054] Adhesion test: Use 2cm wide adhesive tape with a peel strength of not less than 2.74N / cm to firmly stick it on the surface of the film layer. After pulling it up vertically and quickly, if there is no film peeling, it passes the test.

[0055] Wet heat test: Keep the film at 48-52℃ and relative humidity at 95%-100% for 24 hours. The film passes the test if there is no peeling, delamination, cracking, blistering or other defects.

[0056] Temperature test: Keep the temperature at -64 to -60℃ and 68 to 72℃ for 2 hours respectively, then place it at room temperature. The film has passed the test if there is no defect such as peeling, delamination, cracking, blistering, etc.

[0057] Example 2

[0058] The difference from Example 1 is:

[0059] A Φ26mm TQIR chalcogenide glass lens was selected, and the surface layer of one surface of the substrate was bombarded in the wavelength range of 8 to 12 μm using a Kaufman ion source, filled with argon gas, with a gas flow rate of 9 sccm, a bias voltage of 135 V, a discharge voltage of 90 V, a discharge current of 25 A, a coil current of 1.5 A, and bombardment for 6 minutes;

[0060] At 146°C, a 42nm thick CdTe layer, a 128nm thick ZnSe layer, a 328nm thick Ge layer, a 480nm thick ZnSe layer, a 365nm thick Ge layer, a 351nm thick ZnSe layer, a 50nm thick Ge layer, a 1380nm thick ZnSe layer, a 1380nm thick YbF3 layer, and a 200nm thick ZnS layer were deposited in sequence.

[0061] The invention obtains a high-durability anti-reflection film in the 8-12 μm band arranged on a TQIR chalcogenide glass substrate.

[0062] A high-durability anti-reflection film in the 8-12 μm band was coated on both sides of a TQIR chalcogenide glass substrate. The transmittance was measured using a Fourier transform infrared spectrometer, and the average transmittance of the anti-reflection film was found to be 97.23%.

[0063] A high-durability anti-reflection film in the 8-12 μm band was coated on one side of a TQIR chalcogenide glass substrate, and the back side was roughened. The reflectivity was measured using a Fourier transform infrared spectrometer, and the average reflectivity of the anti-reflection film was found to be 0.62%.

[0064] The coated parts were placed in a test box at a temperature of 48-52°C and a relative humidity of 95%-100% for 10 days, and the film layer was observed. There was no film peeling or flaking.

[0065] After the coated parts were placed in a test box at a temperature of 68-72°C and a relative humidity of less than 15% for 48 hours, the film layer was observed and no peeling or other phenomena were observed;

[0066] The coated parts were placed in a test box at a temperature of -42 to -38°C and a relative humidity of less than 15% for 24 hours. Afterwards, the film layer was observed and no peeling or other phenomena were observed.

[0067] The coated parts were tested according to the adhesion, humidity and heat, and temperature test requirements in GJB2585A-2019 "General Specifications for Optical Films". The film layer of the parts passed the adhesion, humidity and heat, and temperature tests. The experimental processes and requirements are as follows:

[0068] Adhesion test: Use 2cm wide adhesive tape with a peel strength of not less than 2.74N / cm to firmly stick it on the surface of the film layer. After pulling it up vertically and quickly, if there is no film peeling, it passes the test.

[0069] Wet heat test: Keep the film at 48-52℃ and relative humidity at 95%-100% for 24 hours. The film passes the test if there is no peeling, delamination, cracking, blistering or other defects.

[0070] Temperature test: Keep the temperature at -64 to -60℃ and 68 to 72℃ for 2 hours respectively, then place it at room temperature. The film has passed the test if there is no defect such as peeling, delamination, cracking, blistering, etc.

[0071] Example 3

[0072] The difference from Example 1 is:

[0073] A Φ28mm TQIR chalcogenide glass lens is selected, and within the wavelength range of 8 to 12 μm, a Kaufman ion source is used to fill argon gas, with a gas flow rate of 12 sccm, a bias voltage of 140V, a discharge voltage of 90V, a discharge current of 35A, a coil current of 3A, and bombardment for 6 minutes on the surface of one surface of the substrate; at 150°C, a 43nm thick CdTe layer, a 126nm thick ZnSe layer, a 329nm thick Ge layer, a 468nm thick ZnSe layer, a 370nm thick Ge layer, a 343nm thick ZnSe layer, a 56nm thick Ge layer, a 1379nm thick ZnSe layer, a 1390nm thick YbF3 layer, and a 207nm thick ZnS layer are sequentially plated. The TQIR chalcogenide glass substrate 8 to 12 μm wavelength band high-durability anti-reflection film of the present invention is obtained.

[0074] A high-durability anti-reflection film in the 8-12 μm band was coated on both sides of a TQIR chalcogenide glass substrate. The transmittance was measured using a Fourier transform infrared spectrometer, and the average transmittance of the anti-reflection film was found to be 97.10%.

[0075] A high-durability anti-reflection film in the 8-12 μm band was coated on one side of a TQIR chalcogenide glass substrate, and the back side was roughened. The reflectivity was measured using a Fourier transform infrared spectrometer, and the average reflectivity of the anti-reflection film was found to be 0.65%.

[0076] The coated parts were placed in a test box at a temperature of 48-52°C and a relative humidity of 95%-100% for 10 days, and the film layer was observed. There was no film peeling or flaking.

[0077] After being kept in a test chamber at a temperature of 68-72°C and a relative humidity of less than 15% for 48 hours, the film layer was observed and no peeling or delamination was observed.

[0078] After being kept in a test box at a temperature of -42 to -38°C and a relative humidity of less than 15% for 24 hours, the film layer was observed and no peeling or delamination was observed.

[0079] The coated parts were tested according to the adhesion, humidity and heat, and temperature test requirements in GJB2585A-2019 "General Specifications for Optical Films". The film layer of the parts passed the adhesion, humidity and heat, and temperature tests. The experimental processes and requirements are as follows:

[0080] Adhesion test: Use 2cm wide adhesive tape with a peel strength of not less than 2.74N / cm to firmly stick it on the surface of the film layer. After pulling it up vertically and quickly, if there is no film peeling, it passes the test.

[0081] Wet heat test: Keep the film at 48-52℃ and relative humidity at 95%-100% for 24 hours. The film passes the test if there is no peeling, delamination, cracking, blistering or other defects.

[0082] Temperature test: Keep the temperature at -64 to -60℃ and 68 to 72℃ for 2 hours respectively, then place it at room temperature. The film has passed the test if there is no defect such as peeling, delamination, cracking, blistering, etc.

[0083] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-durability anti-reflection film in the 8-12 μm band for a TQIR chalcogenide glass substrate, characterized in that: The structure is composed of a CdTe layer, a first ZnSe layer, a first Ge layer, a second ZnSe layer, a second Ge layer, a third ZnSe layer, a third Ge layer, a fourth ZnSe layer, a YbF3 layer, and a fifth ZnS layer, which are stacked in sequence from the surface of the TQIR chalcogenide glass substrate to the air side.

2. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 1, characterized in that: The thickness of the CdTe layer is 40 to 43 nm; The thickness of the first ZnSe layer is 120-128 nm; The thickness of the first Ge layer is 320-329 nm; The thickness of the second ZnSe layer is 468-480 nm; The thickness of the second Ge layer is 365-370 nm.

3. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 1, characterized in that: The thickness of the third ZnSe layer is 345-351 nm; The thickness of the third Ge layer is 50-60 nm; The thickness of the fourth ZnSe layer is 1379-1400 nm; The thickness of the YbF3 layer is 1380-1390nm; The thickness of the fifth ZnS layer is 200-210 nm.

4. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 1, characterized in that: The transmittance of the anti-reflection film is greater than 97%; the reflectivity of the anti-reflection film is less than 0.61%.

5. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 1, characterized in that: The anti-reflection film can withstand an ambient temperature of -42 to 72°C; the anti-reflection film can withstand an ambient relative humidity of less than 15% to 100%.

6. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 1, characterized in that: The preparation method comprises the following steps: Using a Kaufman ion source, bombard any surface of a TQIR chalcogenide glass substrate in a wavelength range of 8 to 12 μm to obtain a film setting surface; A CdTe layer, a first ZnSe layer, a first Ge layer, a second ZnSe layer, a second Ge layer, a third ZnSe layer, a third Ge layer, a fourth ZnSe layer, a YbF3 layer, and a fifth ZnS layer are sequentially stacked on the film setting surface.

7. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 6, characterized in that: During the bombardment of the Kaufman ion source, the gas source used is argon; the gas source flow rate during the bombardment of the Kaufman ion source is 9 to 12 sccm; and the bombardment time is at least 6 minutes.

8. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 6, characterized in that: When bombarding the Kaufman ion source, the bias voltage is 120~140V; the discharge voltage is 80~90V.

9. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 6, characterized in that: The coating temperature of each film layer is 145-150°C.

10. The 8-12 μm band high-durability anti-reflection film for TQIR chalcogenide glass substrate according to claim 6, characterized in that: When bombarded by Kaufman ion source, the discharge current is 25~35A; the coil current is 1.5~3A.

Citation Information

Patent Citations

  • 7.7-14.2 [mu] m waveband DLC protection anti-reflection film of chalcogenide glass substrate

    CN117510095A